Perceraian Menurut Kompilasi Hukum Islam (KHI) dan Fiqh - Nasution, Muhammad Arsad (IAIN Padangsidimpuan, 2018)
This paper tells about divorce, even though it is permissible in Islamic law but it is an act that is hated by Allah Almighty. This solution is given if there is no way out anymore to solve the problems that occur between husband and wife in their household. In the process of implementation there is a dualism of understanding in society. One side of divorce or thalak is the husband's right so he can freely drop it whenever and wherever he wants. This is done, of course, after careful deliberation and peaceful efforts by both husband and wife families. Such provisions are found in the fiqh of fiqh of the Imam of the sect one of which is the fiqh of the Imam Shafi'i sect. Fall of thalak like this is considered legitimate by people who have long held the understanding of the Imam of his school.